The effect and conservation implications of the re-establishment of a Cape fur seal Arctocephalus pusillus pusillus breeding colony at Vondeling Island, Saldanha Bay - Seakamela, Simon Mduduzi (Department of Biological Sciences, 2026)
With regards competition for breeding space, Cape fur seals outcompeted African penguins and Cape cormorants. At the beginning of the study period, African penguins and Cape cormorants had bred in the interior of the island. An interior wall that was built for guano retention had also kept seals out of the interior of the island. This area has suboptimal nesting habitat for penguins (ground nests), which made them vulnerable to destruction by the movement of seals. Bank and crowned (Microcarbo coronatus) cormorants were versatile at utilising island structures (houses and defunct jetty) for breeding which mitigated the potential impact of seal encroachment. The impact on African penguin was mitigated by installation of artificial nests in 2016 which resulted in a marginal increase in breeding pairs. Cape fur seals and African penguins are central place foragers (during breeding) and their foraging distances from colony are restricted by the distribution of their prey. Their core areas were in the vicinity of the island, where the overall overlap was apparent (86%). These core areas extended north of the island for Cape fur seals but south of it for African penguins. These areas were also identified as important biodiversity areas. The high overlap suggests that they compete for forage resources, but the magnitude of competition or mitigation thereof is not clear. Both species likely compete with their conspecifics from other colonies whose published movements suggest an overlap. Home ranges and core areas of Cape fur seals were expectably larger than those of African penguins; 158,486 km2 vs 40,495 km2 and 25,682 km2 vs 7,865 km2 respectively. African penguins were limited to the west coast (southern limit in Cape Point) while Cape fur seals ranged eastwards up to Plettenberg Bay, where another core area was identified. Thus, Cape fur seals can traverse further from the breeding colony during times of poor feeding conditions in the vicinity of their breeding colony. By deduction, Cape fur seals will outcompete African penguins for a resource that has shifted in distribution away from breeding colonies. Furthermore, this dissertation provides a detailed account of a recolonisation event by Cape fur seal at a locality already occupied by seabirds, some of which are endangered. It also demonstrates the importance of concurrent utilisation of long-term datasets in understanding dynamics of marine top predators in a changing environment. It further provides, for the first time, insights into potential at-sea competition for forage resources between sympatric pinniped and seabird species. The results of at-sea competition provide a coarse resolution of a critical question in species interaction within the BCLME. Further research efforts should be built around this foundation to better understand the magnitude of competition between Cape fur seals and African penguins. This could include diet studies that clarifies size and age classes of targeted prey by both species and a combination of horizontal and vertical movement studies to understand the depth at feeding around core areas. Consideration should also be given to the timing of deployment of instruments to capture data describing critical life stages (i.e., breeding, pre-moult, and post-moult periods).